Identifikasi Gaya Arsitektur Islam Timur Tengah Pada Fasad Masjid Haji Muhammad Hanafiah Di Lhoksukon, Aceh Utara - M R Erdiansyah; S M Hassan; A Hendra (Jurnal MESIL (Mesin Elektro Sipil), 2026)
Mosque architecture represents an Islamic cultural expression encompassing aesthetic, symbolic, spiritual, and social values. Its development has been shaped by major Islamic dynasties such as the Umayyad, Fatimid, Ottoman, Safavid, and Mughal, influencing mosque architecture to the present day. In Aceh, mosque architecture has shifted from traditional local forms toward Middle Eastern Islamic visual styles. The Haji Muhammad Hanafiah Mosque in Lhoksukon, North Aceh Regency, exemplifies this transformation through its façade design. This study aims to identify Middle Eastern Islamic architectural styles adopted in the mosque façade and to determine the most dominant influence. A qualitative descriptive method with a comparative approach was employed. The analysis focuses on façade elements, including minarets, domes, walls, ornaments, and arches, examined through form, color, material, and texture variables. The findings reveal that the mosque façade incorporates elements from multiple Islamic dynasties, with the Fatimid architectural style emerging as the most dominant influence.